O cuidado e a ética da transferência : um diálogo entre Freud e Foucault - Zamprogna, Manuela Peixoto (2023)
This master’s research aims to establish connections between the position of the analyst in the transference dynamics, as proposed by Freud, and that of the ancient master in parrhesiastic relationships, based on Foucault's work. The text is structured into three chapters. The first chapter analyzes Freudian transference, considering its developments in the history of the psychoanalytic method, its conceptualization, the risks it implies in the analyst-analysand relationship, Freud's technical recommendations for ethical work with transference, and its implications in terms of the purpose of an analytic experience. The second chapter discusses self-care and spirituality in selected texts from ancient philosophy, the relationships of mastery, and ascetic exercises, from Foucault's perspective, with his course "Hermeneutics of the Subject" (1981-1982) serving as the pivotal reference. The third and final chapter, through a dialogue between Freud and Foucault, examines how transference can be related to ethical and formative relationships, such as those analyzed by Foucault in antiquity. "From Foucault to Freud" seeks to demonstrate critical points from the "Hermeneutics of the Subject" that can be applied to the study of transference, especially regarding the care the analyst needs to exercise upon oneself to ethically deal with such phenomenon. The research concludes that recent studies by Foucault can be a substantive resource for elucidating Freudian conceptions underlying the notion of transference, thus expanding our understanding of the analyst's position and pointing to a potential formative dimension of psychoanalysis.